(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
There are many fulfilling steps in learning a language vocabulary, from the excitement of your first conversation with a fluent speaker to the intellectual challenge of learning actual vocabulary. But at some point, there’s just no way around it: you have to memorize a bunch of words every time you are to speak anything to anyone. So as to find out how many English words know you can take vocabulary tests provided online! While learning English vocabulary lists conventionally is not considered to be glamorous work, every new word gained is another ticket towards making yourself clear. Here are our top vocabulary memorizing methods for how to absorb new English words as efficiently as possible! Maybe one day, future inventories will grant us a way for us to download dictionaries straight into our brains.